SOCIAL CAPITAL REVIEW ON VEGETABLE FARMING (CASE STUDY AT BAROKAH FARMER GROUP SUB-DISTRICT OF TANAH ENAM RATUS SUB DISTRICT OF MEDAN MARELAN) - Mailina Harahap; Surna Herman (JASc (Journal of Agribusiness Sciences), 2017)
Social capital that existed in the community to grow and develop along with the development of human.Modal social built in the interaction of farmers in the container farmer group is a capital that continues to undergo change.Dengan dynamics of vegetable farmers in carrying out farm activities can not be separated from the capital social is built on the life of vegetable farmers. This study aims to find out how social capital contained in vegetable farmers who can be reviewed from the aspect; the farmer's active participation, farmer's belief, social norm and responsibility. Samples of research are vegetable farmer in Barokah Farmer Group of Land Land of Six Ratus.Penelitian use primary data obtained from direct interview with respondent and secondary data. Method of data analysis is tabulation and descriptive analysis by tabulating the frequency of elements of social capital under study. The result of the research shows that all aspects analyzed in social capital consisting of active participation, trust, social norm and dominant responsibility are high. Thus the social capital contained in the Barokah farmer group which is a research sample is a social capital that builds for agricultural development in the research location.Keywords: Social Capital, Farming, Vegetable, Farmer Group